INOVASI PEMBELAJARAN STEM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KOLABORATIF, DAN PROBLEM SOLVING DI ERA INDUSTRI 4.0 - Eka Sartika; Munkizul Umam Kau (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The era of the Fourth Industrial Revolution requires students to possess 21st-century skills, particularly critical thinking, collaboration, and problem solving. STEM (Science, Technology, Engineering, and Mathematics) based learning has emerged as an innovative approach that can address these challenges through the integration of cross-disciplinary concepts and project-based activities. This study aims to analyse the contribution of STEM learning in improving students' higher-order thinking skills through an international literature review. The research method used is a qualitative study based on literature review, with data sources derived from reputable journal articles focusing on STEM implementation and the development of 4C competencies. The results of the study show that STEM learning significantly improves critical thinking skills through scientific investigation and evidence-based analysis; strengthens collaborative skills through structured teamwork; and develops problem-solving skills through the engineering design process and real-world problem solving. However, the implementation of STEM still faces challenges in the form of limited facilities, teacher readiness, and curriculum integration. This study confirms that STEM is a strategic approach in preparing the younger generation to face the demands of Industry 4.0 and is an important foundation for competency-based education reform.